Pediatric in situ lymphoma and Castleman disease – possibility for progression or presence of synchronous diseases - Petrushevska, Gordana; Kocheva, Svetlana; Jovanovska, Aleksandra (EUROPEAN ASSOCIATION FOR HAEMATOPATHOLOGY, 2024)
A child, 7.5 years old with a history of previously diagnosed Pediatric In Situ Folicullar Lymphoma, treated by ‘watch and wait’ strategy has been admitted at the Pediatric University Clinic, Skopje, in February 2023. In June 2022, due to worsened generalised lymphadenopathy (No.1206640) and symptoms of anaemia, thrombocytopenia and slight splenomegaly, new lymph node biopsy has been done.. The obtained diagnosis was Atypical Lymphoid Hyperplasia. In February 2023, the child was again admitted to the hospital with signs of coughing and dyspnea. On physical examination there were found increased cervical lymph nodes and metabolic disease in the mediastinal and abdominal lymph nodes as well as in the spleen and lung parenchyma.